KUALITAS ARSITEKTURAL UNIT HUNIAN DENGAN LUAS MINIMAL DI RUMAH SUSUN PASAR JUMAT - Bertha Antono (TATANAN, 2008)
Abstract Low Cost Apartment is one of the solutions in solving the city's problem as the limited space also the increasing of the residence's needs. But the low cost apartment is usually made for the middle-low class community, oftentimes they ignores the quality of the architecture sector itself in order to compress the expense. While in every residence, the occupants always try to find the residence's place which has qualities with the reasonable price. By having this research, can be seen how far some simple low cost apartment can the architecture's qualities which is adequate even though the space is limited. The case which is chosen is the Pasar Jumat Low Cost Apartment. Pasar Jumat Low Cost Apartment is held on the Jakarta city and have one type unit which is type 21. The understanding of this architecture's quality contains of some important aspects. Those aspects are the space's qualities, lightings, circulations, utilities and also the esthetics. The most important aspects based on the minimal space in some residence are the space's qualities, lightings, and circulations. But all those aspects are still influence how some residence is graded as the qualities one or not, by making the combination from some other factor as the occupants and also the rules of those developers themselves.  Key words: architecture's qualities, low cost apartment's unit, minimal space  Abstrak Rumah susun merupakan salah satu solusi dalam menangani masalah perkotaan atas keterbatasan lahan maupun peningkatan kebutuhan hunian. Namun rumah susun sederhana yang pada umumnya ditujukan untuk kalangan menengah ke bawah, seringkali mengabaikan segi kualitas arsitektural sendiri guna menekan biaya. Sedangkan untuk setiap tempat tinggal, penghuni senantiasa mencari hunian berkualitas dengan harga terjangkau. Melalui penelitian ini dilihat sejauh mana suatu rumah susun sederhana mampu menghadirkan kualitas arsitektural yang memadai walaupun dengan luas yang cukup terbatas. Studi kasus yang dipilih adalah Rumah Susun Pasar Jumat. Rumah Susun Pasar Jumat ini berada di kota Jakarta dan memiliki satu jenis unit yaitu type 21. Pengertian kualitas arsitektural di sini mencakup beberapa aspek penting. Aspek-aspek tersebut adalah kualitas ruang, pencahayaan, sirkulasi, utilitas dan juga estetika. Aspek yang paling berperan penting sehubungan dengan luas minimal suatu hunian adalah kualitas ruang, pencahayaan dan sirkulasi. Namun keseluruhan aspek tersebut tetap mempengaruhi bagaimana suatu hunian dinilai berkualitas atau tidak, dengan mengkombinasikan beberapa faktor penentu lain seperti penghuni maupun peraturan pengelola sendiri.  Kata kunci: kualitas arsitektural, unit hunian rumah susun, luas minimal